O tratamento do conteúdo informacional da fotografia na Arquivística: algumas reflexões - Silva, Irisneide de Oliveira Souza [UNESP]; Dal'Evedove, Paula Regina [UNESP]; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2010)
In the contemporary society, the recurring preoccupation about the effective use and appropriation of information has forced a progressive maturing of Information Science and its extention to new fields of study. In archival management, some gaps can be found concerning the treatment of photographs that have not been solved either theoretically or methodologically. This study approaches one of these gaps: the one related to the processing of the informational content of the photographic documents in archives. After a literature review, several recommendations are proposed regarding the identification, organization, representation, retrieval and access to the informational content of photographs in archives.

En la sociedad contemporánea, la preocupación recurrente por el uso efectivo y la apropiación de la información ha exigido una maduración gradual de la Ciencia de la Información y su posicionamiento en nuevas áreas. En el campo de la Archivística, el tratamiento de las fotografías presenta todavía varias lagunas teóricas y metodológicas. Este estudio aborda las referentes al proceso de tratamiento del contenido informacional de los documentos fotográficos en archivos. A partir de un análisis de la literatura, se proponen diversas recomendaciones para mejorar la identificación, organización, representación, recuperación y acceso a los contenidos informacionales de las fotografías en fondos archivísticos.
The treatment of photographic informational content in archival management: some considerations
El tratamiento del contenido informativo de la fototografia en Archivistica: algunas reflexiones
Keywords: fotografias; arquivos; arquivologia; tratamento temático da informação